Significant N2O emission from a high rate granular reactor for completely autotrophic nitrogen removal over nitrite. (15th July 2020) - Fang, Fang; Li, Hanxiang; Jiang, Xin; Deng, Xiongwen; Yan, Peng; Guo, Jinsong; Chen, Youpeng; Yang, Jixiang
Abstract: Expanded granular sludge bed (EGSB) reactors were rarely applied for complete ammonium removal over nitrite. In this study, a high ammonium loading rate of 3677 mg N/L/d was achieved in an EGSB reactor. Approximately 5.5–8.5% of influent ammonium was converted to nitrous oxide (N2 O) that is a potent greenhouse gas. Moreover, the percentage increased linearly with the increase in ammonium load. A model well matched the reactor dynamics. The model indicated that hydroxylamine (NH2 OH) oxidation contributed to over 40% of produced N2 O, and denitrification by ammonium oxidizing bacteria contributed to N2 O emission significantly. Furthermore, the model suggests that a low oxygen concentration can result in a low N2 O emission at the cost of a slightly low ammonium removal rate while influent organic matter play a minor role in reducing N2 O emission. This study shows that EGSB reactors are effective in ammonium removal. In addition, the emission of N2 O is significant. Graphical abstract: Image 1 Highlights: A high ammonium loading rate of 3677 mg N/L/d was achieved at low DO concentrations. The produced N2 O accounted for 5.5%–8.5% of the influent ammonium. A comprehensive model was established for modeling N removal. NH2 OH oxidation contributed much more N2 O than heterotrophic bacteria. A low oxygen concentration (<0.2 mg/L) would result in a low N2 O emission.